Sensitivity Enhancement of Fault Detection Utilizing Feedback Compensation for Time-Delay Signature of Chaotic Laser - Haoran Guo; Hui Liu; Min Zhang; Xiaomin Guo; Yuanyuan Guo; Hong Han; Tong Zhao (Photonics)
Fiber fault detection based on the time-delay signature of an optical feedback semiconductor laser has the advantages of high sensitivity, precise location, and a simple structure, which make it widely applicable. The sensitivity of this method is determined by the feedback strength inducing the nonlinear state of the laser. This paper proposes a feedback compensation method to reduce the requirement of the fault echo intensity for the laser to enter the nonlinear state, significantly enhancing detection sensitivity. Numerical simulations analyze the impact of feedback compensation parameters on fault detection sensitivity and evaluate the performance of the laser operating at different pump currents. The results show that this method achieves a 9.33 dB improvement in sensitivity compared to the original approach, effectively addressing the challenges of detecting faults with high insertion losses in optical networks.